Cross-cultural adaptation of the Brazilian version of the Dentine Hypersensitivity Experience Questionnaire (DHEQ-15) - Dhelfeson Willya Douglas-; Frederico Santos Lages; Saul Martins Paiva; Jennifer Grace Cromley; Peter Glenn Robinson; Luís Otávio Miranda Cota (Sociedade Brasileira de Pesquisa Odontológica, 2018)
Abstract The dentine hypersensitivity (DH) is able to impair the oral health related quality of life (OHRQoL). However, there isn't any specific validated questionnaire to be used in Brazil. The objective was to adapt and to validate the English version of the Dentine Hypersensitivity Experience Questionnaire (DHEQ-15) for use in Brazil. DHEQ-15 was cross-culturally adapted into the Brazilian-Portuguese language and then validated in a cross-sectional study with 100 participants recruited at a University clinic. Study sample comprised 2 groups: 100 individuals with DH, and 100 individuals without. The instrument was self-administered twice 7 to 10 days apart. The participants answered a global rating of oral health. The psychometric properties of the Brazilian version of DHEQ-15 were verified through internal consistency (Cronbach's α) and test-retest reliability (intraclass correlation coefficient - ICC), convergent (Spearman correlation) and discriminant (Mann-Whitney test) validity. The significance threshold was set at p<0.05. Sample comprised 69 men and 131 women, of mean age 30.4y. The Brazilian DHEQ-15 demonstrated very good internal consistency (α = 0.945). Test-retest reliability revealed excellent reproducibility (ICC = 0.959, p < 0.001). There was statistically significant correlation between the scores obtained on all DHEQ-15 domains and the global rating of oral health (p<0.001). Participants with DH scored significantly higher than those without DH (p<0.001). This study provides evidence supporting the cross-cultural validity of the Brazilian version of DHEQ-15 for use in Brazil.